The MMP-1/PAR-1 Axis Enhances Proliferation and Neuronal Differentiation of Adult Hippocampal Neural Progenitor Cells. (13th December 2015) - Valente, Maria Maddalena; Allen, Megan; Bortolotto, Valeria; Lim, Seung T.; Conant, Katherine; Grilli, Mariagrazia
Abstract : Matrix metalloproteinases (MMPs) are zinc-dependent endopeptidases that play a role in varied forms of developmental and postnatal neuroplasticity. MMP substrates include protease-activated receptor-1 (PAR-1), a G-protein coupled receptor expressed in hippocampus. We examined proliferation and differentiation of adult neural progenitor cells (aNPCs) from hippocampi of mice that overexpress the potent PAR-1 agonist MMP-1. We found that, as compared to aNPCs from littermate controls, MMP-1 tg aNPCs display enhanced proliferation. Under differentiating conditions, these cells give rise to a higher percentage of MAP-2 + neurons and a reduced number of oligodendrocyte precursors, and no change in the number of astrocytes. The fact that these results are MMP and PAR-1 dependent is supported by studies with distinct antagonists. Moreover, JSH-23, an inhibitor of NF- κ B p65 nuclear translocation, counteracted both the proliferation and differentiation changes seen in MMP-1 tg-derived NPCs. In complementary studies, we found that the percentage of Sox2 + undifferentiated progenitor cells is increased in hippocampi of MMP-1 tg animals, compared to wt mice. Together, these results add to a growing body of data suggesting that MMPs are effectors of hippocampal neuroplasticity in the adult CNS and that the MMP-1/PAR-1 axis may play a role in neurogenesis following physiological and/or pathological stimuli.